Ultrasonic investigations of inclusion complexes of α-cyclodextrin with amphiphil substances - JUSZKIEWICZ, A.; BALCERZAK, A. (Archives of Acoustics, 1993)
Velocity and attenuation measurements of ultrasonic waves in water solutions of α-cyclodextrin containing different amphiphil substances: sodium octyl sulfate (SOS0), sodium decyl sulfate (SDeS), decylpyridinium bromide (DePyB) and sodium caprinate (SCp) were made. The occurrence of an ultrasonic relaxation process connected with the formation of inclusion complexes of α-cyclodextrin with SDeS, DePyB, SCp was established.